Health promotion competencies for Australia 2001-5: trends and their implications - Shilton, T.; Howat, Peter; James, R.; Burke, Linda; Hutchins, C.; Woodman, R. (International Union for Health Promotion and Education, 2008)
This important research builds on past projects in Australia and internationally that have sought to define and clarify competencies required to work in health promotion. The paper briefly explains the process undertaken in 2005 to update the Australian health promotion competencies as a collaboration of several leading health promotion agencies. The article reports findings from research undertaken in 2001 and 2005 and compares trends in perceptions of health promotion competencies across time. This dialogue among researchers, health promotion academics and practitioners can help to further the impact of competencies research on professional practice in health promotion globally. This project placed a priority on methodology that engaged the health promotion workforce in Australia. A two-stage process was employed including expert consultation with 39 senior health promotion professionals, followed by a modified Delphi process to engage 400 practitioners.Space was allowed for comment on the competencies including suggested word changes, and respondents were also invited to add additional competencies. The research involved a modified Delphi study where participants were invited to rate each competency as “essential”, “desirable” or “not relevant”, and to suggest changes to wording, as well as additions to the list. Responses were received from 400 practitioners and the results were presented and compared with the 2001 survey results. Results indicate a substantial shift in perceptions about health promotion practice in Australia during the initial years of the 21st century.The overall significant changes in perceptions indicate that by 2005 the Australian health promotion workforce had substantially moved away from an individual behaviour-dominated perception of health promotion practice. Increasing recognition was given to competencies that reflect environmental, economic and policy influences on health, and increased recognition that these processes are legitimate and essential components of the health promotion process. (Promot Educ 2008; 15(2): 21—26)